Policy narratives help maintain institutional traps in the governance of floods in Thailand - Louis Lebel (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group The governance of floods in urbanizing regions of Thailand is significantly constrained by institutional traps. Comparisons of the impacts and governance responses to major flood events in Chiang Mai, Ayutthaya and Bangkok in 2005–06 and 2011 suggests that there has been very little policy learning. Institutional traps remain as important now as they were more than a decade ago. Dominant policy narratives help maintain institutional traps by promoting solutions that reduce organizational risks, like the transfer of responsibilities to local communities, or reflect organizational interests and professional norms. Policy narratives will need to be challenged or transformed if progress in building urban resilience to floods is to be made.